2013
DOI: 10.4196/kjpp.2013.17.5.427
|View full text |Cite
|
Sign up to set email alerts
|

Activation of G Proteins by Aluminum Fluoride Enhances RANKL-Mediated Osteoclastogenesis

Abstract: Receptor activator of NF-κB ligand (RANKL)-induced osteoclastogenesis is accompanied by intracellular Ca2+ mobilization in a form of oscillations, which plays essential roles by activating sequentially Ca2+/calmodulin-dependent protein kinase, calcineurin and NFATc1, necessary in the osteoclast differentiation. However, it is not known whether Ca2+ mobilization which is evoked in RANKL-independent way induces to differentiate into osteoclasts. In present study, we investigated Ca2+ mobilization induced by alum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 35 publications
2
2
0
Order By: Relevance
“…However, their data compared mRNA levels but not cellular Gq activity, which for GTPases is a more relevant readout. In support of our findings, other scientists suggest that activation of G proteins by AlF4 treatment activates osteoclast differentiation ( 60 ) and that elevated expression of Gq in osteoblasts increases osteoclastogenesis in a transgenic mouse model ( 61 ). New therapeutic tools to inhibit G protein signaling are currently being characterized, and it remains to be seen whether they will provide helpful tools in the treatment of auto-inflammatory diseases such as RA as well ( 62 ).…”
Section: Discussionsupporting
confidence: 90%
“…However, their data compared mRNA levels but not cellular Gq activity, which for GTPases is a more relevant readout. In support of our findings, other scientists suggest that activation of G proteins by AlF4 treatment activates osteoclast differentiation ( 60 ) and that elevated expression of Gq in osteoblasts increases osteoclastogenesis in a transgenic mouse model ( 61 ). New therapeutic tools to inhibit G protein signaling are currently being characterized, and it remains to be seen whether they will provide helpful tools in the treatment of auto-inflammatory diseases such as RA as well ( 62 ).…”
Section: Discussionsupporting
confidence: 90%
“…Notably, the activity of NFATc1 are known to be regulated by Ca 2+ signaling relied on the tyrosine phosphorylation pathways. 4,25 In this study, vitamin K 1 treatment slightly enhanced the RANKL-induced Ca 2+ oscillation, whereas MK-4 and MK-7 reduced the frequency of Ca 2+ oscillations in BMMs (Fig. 5).…”
Section: Discussionsupporting
confidence: 48%
“…Accumulated evidence has revealed that RANKL-induced [Ca 2+ ] i oscillations require orchestration of Ca 2+ mobilization from internal and external Ca 2+ stores [ 7 , 11 13 ]. Especially, our previous work indicated that release of Ca 2+ from inositol 1,4,5-trisphosphate (IP 3 )-sensitive Ca 2+ stores and influx of extracellular Ca 2+ via store-operated Ca 2+ channels (SOCCs) are both essential for building up RANKL-induced [Ca 2+ ] i oscillations [ 7 ].…”
Section: Resultsmentioning
confidence: 99%